Cross-talk between mitochondria and proteasome in Parkinson's disease pathogenesis - Martins Branco, Diogo; Arduino, Daniela M.; Esteves, A. Raquel; Silva, Diana F.; Cardoso, Sandra M.; Oliveira, Catarina (Frontiers in Aging Neuroscience, 2010)
Parkinson’s disease (PD) is the most common progressive neurodegenerative movement disorder, characterized by the selective loss of nigrostriatal dopaminergic neurons, and the presence of intracellular insoluble proteinaceous inclusions, known as Lewy Bodies. Although PD etiopathogenesis remains elusive, the leading hypothesis for the death of specific groups of neurons establishes that mitochondrial dysfunction, alterations in the ubiquitin-proteasomal system (UPS), and oxidative stress are major events that act synergistically causing this devastating disease. In this review we will focus on mitochondrial impairment and its implications on proteasomal function and alpha-synuclein aggregation. We will address the role of mitochondria and proteasome cross-talk in the neuronal loss that leads to PD and discuss how this knowledge might further improve patient therapy.